Reforms of the administration of provision – selected directions of change and development in the sphere of public education and social welfare - Cendrowicz, Dominika; Raszewska-Skałecka, Renata (Studia Iuridica Toruniensia, 2023)
The aim of the article is the analysis and evaluation of selected directions of changes and development in servicing public administration on the example of public education and social welfare. The article offers an attempt to formulate conclusions on selected directions of public administration reforms in the indicated areas of its activity. The questions will be answered as to where the impulses for reforming public administrationntoday come from, and what mechanisms trigger and influence the reforms of public administration in the selected areas of its activity.